Pregnant women of advanced maternal age have higher central arterial stiffness than younger pregnant women throughout pregnancy and postpartum - Lee, Ruda; Santillan, Mark K; Santillan, Donna A; Stroud, Amy K; Nuckols, Virginia R; DuBose, Lyndsey E; Holwerda, Seth W; Luehrs, Rachel E; Betz, Alexandria M; Brandt, Debra; Pierce, Gary L; Stanhewicz, Anna E (Journal of applied physiology (1985), 2025)
Pregnancy at advanced maternal age (AMA, ≥35 yr) is increasingly common in developed countries. Delayed pregnancy may elevate the risk of adverse pregnancy outcomes, such as hypertensive disorders, potentially due to altered arterial structure and function or insufficient vascular adaptations during pregnancy. Therefore, this study aimed to characterize differences in maternal vascular and autonomic function across pregnancy and postpartum in healthy pregnant women of AMA compared with younger pregnant women by retrospectively analyzing data from 57 younger pregnant women (21-30 yr; 27 ± 3 yr) and 22 pregnant women of AMA (≥35 yr; 36 ± 1 yr). Arterial stiffness, remodeling, and endothelial function were assessed using carotid-femoral and carotid-brachial pulse wave velocity (cfPWV and cbPWV), carotid β-stiffness, carotid intima-media thickness (IMT), and brachial artery flow-mediated dilation (FMD) in the first, second, and third trimesters and postpartum (4-14 wk). Beat-to-beat blood pressure variability (BPV), cardiovagal baroreflex sensitivity (BRS), and heart rate variability (HRV) were also assessed. The AMA group exhibited higher cfPWV, cbPWV, β-stiffness, and IMT compared with the younger group during pregnancy ( ≤ 0.03), with cfPWV and cbPWV remaining higher in the postpartum period ( ≤ 0.01). The AMA group also had higher systolic BPV, lower BRS, and lower HRV compared with the younger group during pregnancy ( ≤ 0.04), with consistently lower BRS postpartum ( < 0.01). Blood pressure and FMD did not differ between groups throughout pregnancy and postpartum ( ≥ 0.27). These findings suggest that women of AMA have higher central arterial stiffness and altered autonomic function throughout pregnancy, which may contribute in part to increased risk of pregnancy complications. This study assessed the impact of advanced maternal age (AMA) on vascular and autonomic function across all three trimesters. Compared with younger pregnant women, women of AMA exhibited higher arterial stiffness and greater carotid intima-media thickness, and impaired autonomic regulation throughout pregnancy, despite no significant difference in endothelial function. These observed differences may represent early subclinical changes in AMA women, which may bring them closer to a physiological threshold where complications may occur.